2015
DOI: 10.1002/ece3.1620
|View full text |Cite
|
Sign up to set email alerts
|

An experimental test on time constraint and sexual conflict over parental care

Abstract: Because parental care is costly, a sexual conflict between parents over parental investment is expected to arise. Parental care behavior is an adaptive decision, involving trade-offs between remating, and consequently desertion of the brood, and continuing parental effort. If the main advantage of desertion is remating, then this will be a time constraint, because the deserting individual will require a certain minimum period of time to breed again in the same breeding season. So, a short breeding season shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…This pattern also has been proven in insects and fish, where males extend the duration of parental care when they are experiencing intensive competition (Grüter and Taborsky 2005;Hopwood et al 2015). Second, in a migratory species with a short breeding season, such as rock sparrow, individual parental care decisions may be restricted by the amount of time remaining in the season (Griggio 2015). In this study, we found the number of males in the mating pool declined after day 60.…”
Section: Seasonal Variation In Male Parental Care and Mating Opportunitysupporting
confidence: 74%
“…This pattern also has been proven in insects and fish, where males extend the duration of parental care when they are experiencing intensive competition (Grüter and Taborsky 2005;Hopwood et al 2015). Second, in a migratory species with a short breeding season, such as rock sparrow, individual parental care decisions may be restricted by the amount of time remaining in the season (Griggio 2015). In this study, we found the number of males in the mating pool declined after day 60.…”
Section: Seasonal Variation In Male Parental Care and Mating Opportunitysupporting
confidence: 74%
“…ref. 9 15 ). For example in some cichlid fish, males are more likely to desert their brood when opportunities to breed are high 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the Kentish plover, Charadrius alexandrinus, much depends on the current operational sex ratio in the adult population, and since it is often male-biased, females have a higher chance for successful remating, and so they are the deserting sex (Blashine and Blomqvist 1999;Pilastro et al 2001;Webb et al 2002). Opportunity for re-mating, however, reduces with progress of the breeding season (Szekely and Cuthill 2000;Griggio 2015) and for single-brooded species is non-existent. Examining such species may actually help to understand the most basic conditions for brood desertion.…”
Section: Introductionmentioning
confidence: 99%